Exploring the demographic and contextual factors influencing English language teachers’ burnout: implications for teacher education programs - Navidinia, Hossein; Heiran, Akbar (Penerbit Universiti Kebangsaan Malaysia, 2017)
The study aimed to investigate and compare the demographic and contextual factors influencing the level of burnout of English as a Foreign Language (EFL) teachers teaching at Iranian Public Schools (IPS) and Private Language Institutes (PLI). To this end, both quantitative and qualitative methods of gathering data were used. 100 EFL teachers participated in the quantitative phase. They were asked to complete “Maslach Burnout Inventory” and to write their demographic information. Data were analyzed using independent sample T-tests. The results of T-tests showed that IPS teachers with higher educational degrees had higher levels of burnout. A significant difference in the level of burnout were also found among teachers with different years of teaching experience, however, no significant difference was found between female and male teachers’ level of burnout. In the qualitative phase of the study and in order to identify the contextual factors influencing teacher burnout, semi-structured interviews were conducted with 16 EFL teachers who were identified as “burnout teachers” based on the results of the first phase of the study. Low salary, heavy workload, teacher evaluation procedure, lack of teacher autonomy, student misbehavior, shortage of facilities, and time pressure were identified as some factors leading to teacher burnout.